Squeeze This! : A Cultural History of the Accordion in America - Jacobson, Marion S. (Book collections on Project MUSE., 2012)
Squeeze This! is the first history of the piano accordion and the first book-length study of the accordion as a uniquely American musical and cultural phenomenon.